Intestinal Type Borderline Mucinous OvarianTumour - Shakya, B (Journal of Nepal Health Research Council, 2014)
A 26 years old para 4 lady presented with abdominal distension following a home delivery 18 months back and lactationalamenorrhoea following since. Examination and investigation findings revealed a large ovarian tumour(28X28 cm) occupying the whole of the abdomen. Tumour markers were normal except for a slightly raised lactate dehydrogenase enzyme. Patient underwent staging laparotomy- left salpingoophorectomy, right tubal ligation with omental biopsy and peritoneal fluid cytology. Histopathology report revealed borderline mucinous ovarian tumour of intestinal type. Her postoperative period was uneventful and she was advised for follow-up. Borderline ovarian tumours are uncommon tumours. In the younger age with stage I, fertility sparing surgery is enough and has excellent prognosis, but follow up is important.Â Keywords: borderline ovarian tumour; follow-up, prognosis